Relationship between sarcopenia and the serum creatinine/cystatin C ratio in Japanese rural community‐dwelling older adults. Issue 1 (1st January 2018) - Kusunoki, Hiroshi; Tsuji, Shotaro; Wada, Yosuke; Fukai, Mayuka; Nagai, Koutatsu; Itoh, Masako; Sano, Kyoko; Tamaki, Kayoko; Ohta, Yoshinori; Amano, Manabu; Maeda, Hatsuo; Hasegawa, Yoko; et al.
Abstract: Aims: Sarcopenia, the age‐related decline in skeletal muscle volume and function, is associated with negative clinical and socioeconomic outcomes in elderly people. Clinical biomarkers to diagnose sarcopenia that can be quantified in a reliable, and cost‐ effective manner, are needed. We investigated whether the creatinine (Cr) /cystatin C (CysC) ratio is correlated with muscle volume and physical function in Japanese community‐dwelling elderly subjects. Methods and results: The present study included 213 men aged 73.2±6.2 years and 464 women aged 72.4±5.5 years from a rural area in the Hyogo prefecture of Japan. To evaluate whether the Cr/CysC ratio is correlated with sarcopenia criteria in elderly individuals without severe renal impairment, we excluded subjects with estimate glomerular filtration rate (eGFR) <45. The prevalence of sarcopenia diagnosed according to the AWGS criteria was 2.8% in men and 3.4% in women. The Cr/CysC ratio correlated with skeletal mass index (r = 0.49, p <0.0001), skeletal muscle mass (r = 0.53, p <0.0001), grip power (r = 0.59, p <0.0001), knee extension muscle strength (r = 0.49, p <0.0001), normal gait speed (r = 0.18, p <0.0001), and maximal gait speed (r = 0.32, p <0.0001). A negative correlation between the Cr/CysC ratio and, body fat mass (r = −0.20, p <0.0001) and percentage of body fat mass (r = −0.39, p <0.0001) was observed. In a multiple regression analysis, Cr/CysC was also found to be significantly positively correlated with each component of the sarcopenia criteria. Conclusions: Even in elderly individuals without severe renal impairment, the Cr/CysC ratio was positively correlated with muscle volume and physical function and negatively correlated with body fat mass. Therefore, the Cr/CysC ratio might be a useful biomarker to predict sarcopenia.